DNA damage repair-related methylated genes RRM2 and GAPDH are prognostic biomarkers associated with immunotherapy for lung adenocarcinoma - Xinru, Mao; Shaban Eljali, Saad; Lee, Nung Kion; Isabel Lim, Fong (Sociedade Brasileira de Genética (Brazilian Society of Genetics), 2025)
Research has highlighted the significant role of methylated genes associated with DNA damage repair in pathogenesis of Lung adenocarcinoma (LUAD). However, the potential of DNA damage repair-related gene (DDRG) methylation as a prognostic biomarker remains underexplored. This study aimed to assess the prognostic value of methylated DDRGs in LUAD. Analysis of the TCGA-LUAD dataset revealed differentially expressed genes (DEGs) and differentially methylated genes (DE-MGs), from which methylated DE-DDRGs were identified. An independent prognostic risk model was constructed based on these methylated DE-DDRGs by integrating risk scores with clinical features. Additionally, the study examined responses to immunotherapy. Results indicated that CLU exhibited hypermethylation and elevated expression in LUAD tissues, while eight other genes (BUB1B, SHCBP1, RRM2, RPL39L, TRIP13, GAPDH, ENO1, and CENPM) showed high expression and hypomethylation. Among these, RRM2 and GAPDH were significantly linked to poorer overall survival. Furthermore, single-sample gene set enrichment analysis (ssGSEA) revealed that patients with LUAD in the high-risk group had lower immune scores and less immune cell infiltration. TIDE analysis suggested that patients in the low-risk group may exhibit greater sensitivity to immune checkpoint inhibitor therapy. In conclusion, RRM2 and GAPDH represent promising prognostic and immunotherapeutic biomarkers, offering new avenues for LUAD treatment strategies.